Microtexturing for Enhanced Machining: Evaluating Tool Performance in Laser-Processed Cutting Inserts - Bilek, Ondrej; Ondrik, Jan; Janik, Petr; Kautsky, Tomas (Manufacturing Technology Journal, 2024)
This article explores the significance of microtexturing on cutting tools for improved tribological performance and reduced friction in machining operations. Drawing inspiration from biomimetic structures, the study focuses on laser surface microtexturing and evaluates its impact on cutting forces and tool wear. Experiments involve microtextures of dots with a specific emphasis on a fiber laser-processed pattern. While long-term tests reveal the formation of negative protrusions on the textured tools, reduced variability in cutting forces suggests potential benefits for stable machining processes and increased tool longevity. The findings underscore the intricate relationship between microtexturing patterns and tool performance, offering insights into the broader implications for energy-efficient machining.
Keywords: Microtexturing; Tribology; Laser Surface Processing; Cutting Forces; Cutting Tool